唐代的体育文化与体育诗创作探究: An Exploration of Sports Culture and Sports Poetry Creation in the Tang Dynasty - Shen Qi; Fan, Pik Wah (ERUDITE: Journal of Chinese Studies and Education, 2024)
唐代体育文化以其绚丽多姿的艺术展现其深厚丰富的审美内涵，不仅为唐代诗歌赋予了更为独特的艺术风貌，更极大地拓展了诗歌创作的题材领域。综合运用体育学、文学、历史学等多学科的理论与研究方法，对唐代体育题材诗进行分析和研究，力求全面揭示唐代国力鼎盛、文化繁荣的社会背景下，体育生活的多姿多彩与丰富内涵。唐代形式多样的体育运动，不仅有助于民众强身健体，其所蕴含的多元审美体验更是极大地丰富了诗歌的题材内容，推动了诗歌艺术的创新与发展。唐代体育诗以凝炼的文字展现了唐代精湛的表演艺术与体育文化的融合，堪称记录唐代各类体育运动的重要脚本，为后世提供了再现唐代体育技艺高超水平的宝贵资料。 Tang Dynasty sports culture, with its diverse artistic forms and profound and rich aesthetic connotations, gave Tang Dynasty poems a unique artistic style and greatly expanded the subject areas of poetic creation. By comprehensively applying the theories and research methods of sports, literature, history, and other disciplines, we analyze and study Tang Dynasty poems with sports themes, aiming to comprehensively reveal the colorful and rich connotations of sports life in the context of Tang Dynasty’s social background of national strength and cultural prosperity. The various forms of sports helped people to be physically fit and greatly enriched the subject matter of poems with the diverse aesthetic experiences they contained. It also promoted the innovation and development of poetic art. The sports poems show the fusion of the Tang Dynasty’s superb performing arts and sports culture with condensed words, which can be called an essential script for recording all kinds of sports in the Tang Dynasty, and provide valuable information for future generations to reproduce the high level of Tang Dynasty’s sports skills. Keywords: Sports Poetry, Tang Dynasty sports, sports culture, interdisciplinary research